High density plasma sources design, physics, and performance - Popov, Oleg A. (Noyes Publications, 1995)
This book describes the design, physics, and performance of high density plasma sources which have been extensively explored in low pressure plasma processing, such as plasma etching and planarization, plasma enhanced chemical vapor deposition of thin films, sputtered deposition of metals and dielectrics, epitaxial growth of silicon and GaAs, and many other applications. This is a comprehensive survey and a detailed description of most advanced high density plasma sources used in plasma processing.
Keywords: Plasma density.; High temperature plasmas.; Plasma generators.; elektronické knihy; electronic books